Design and Performance of a SAW Ladder-Type Filter at 3.15 GHz Using SAW Mass-Production Technology - Springer, Andreas; Hollerweger, Franz; Weigel, Robert; Berek, S.; Thomas, Ralf; Ruile, Werner; Ruppel, Clemens; Guglielmi, Marco (IEEE Transactions on Microwave Theory and Techniques, 1999)
To meet the increasing demand for highperformance filters in gigahertz radio-communication systems, we have improved the design techniques and fabrication processes for surface-acoustic wave (SAW) devices. The standard optical projection printing technique based on i-line lithography used for mass-production was optimized, thus attaining a linewidth of 0.3 _m. As a first SAW device prototype, we designed and fabricated a ladder-type bandpass filter from LiTaO3 substrates, at 3.15 GHz having a 3 dB-bandwidth of 128 MHz and a minimum insertion loss of 1.7 dB.
elib2cris::1512001600,springer1999a
Keywords: Ladder-type filter; SAW process technology; surface-acoustic wave filters